The Effect of Cyber security Knowledge on Employees Personal Growth: An empirical Study in private hospitals in Libya and Yemen - Ali A.M.A.; Musaed A.-M.M.N.; Alias R.B. (Tarbiat Modares University, 2023)
This paper focused on the effect of cyber security knowledge CSK on employees personal growth PG in private hospitals in Libya and Yemen. Employees were evaluated for their responses to cyber practice, cyber threats targeting end-users in the healthcare industry (i.e., malware, social engineering, spam, phishing, and ransomware), and cyber awareness. The descriptive analytical approach was used to determine the relationship between the independent CSK and dependent variable PG, the current study took place in March 2021 and was applied to a stratified random sample of 164 managers from the middle and lower management. Results indicated a lack of understanding of cyber threats and recommended mitigations and uncertainty regarding applicable legislation governing electronic patient information; also, the level of CSK & PG in the studied hospitals was low. The findings also show that CSK positively affects employees PG beyond the demographic differences in respondents. Finally, a set of recommendations for effective based cyber security implementations and training programs were presented and discussed. 2022, Tarbiat Modares University. All rights reserved.